Anonymous
Anonymous asked in Science & MathematicsMathematics · 12 months ago

# The equation is 13k = 6k/15t - 7t Make k the subject?

Relevance
• 12 months ago

13 k = 6 k/15 t - 7t

13 k = (2 k t)/5 - 7 t

65 k = t (2 k - 35)

k(65 - 2 t) = -35 t

k

= -35 t / (65 - 2 t)

= 35 t / (2 t - 65)

• ?
Lv 7
12 months ago

13k = 6k/15t - 7t

// Multiply through by 15t

13k (15t) = 6k - 7t (15t)

195 kt - 6k = - 105 t²

// Factor out k

k (195t - 6) = -105 t²

// Divide through by (195t - 6)

k = -105 t² / (195t - 6)....................ANS

• Como
Lv 7
12 months ago

Presentation is open to doubt due to lack of brackets.

• Random Stranger
Lv 6
12 months agoReport

No it isn't! That's why we use the order of operations, to prevent ambiguity. Asker my have asked the wrong question but what was asked is NOT in doubt.

• 12 months ago

I assume that the - 7t is a separate term

in other words, your equation is NOT:

13k = 6k / (15t - 7t)

-----

13k = (6k/15t) - 7t

multiply both sides by (15t)

(13k)(15t) = 6k - (15t)(7t)

clean up

195kt = 6k - 105t^2

subtract 6k from both sides

195kt - 6k = -105t^2

factor out "k" on the left

k(195t - 6) = -105t^2

divide both sides by (195t - 6)

k = (-105t^2) / (195t - 6)

• 12 months ago

Presuming you mean:

13k = 6k/(15t) - 7t

Since "k" is in more than one term, we need to group them together. Start with multiplying both sides by the denominator (15t):

195kt = 6k - 105t²

Now move the terms with "k" to one side and all other terms to the other side:

195kt - 6k = -105t²

to simplify a little, multiply both sides by -1. I'll flip the two terms around the subtraction on the left side:

6k - 195kt = 105t²

And now I can divide both sides by 3 to simplify further before we move on:

2k - 65kt = 35t²

Now we can factor out the k:

k(2 - 65t) = 35t²

and divide:

k = 35t² / (2 - 65t)